2009
DOI: 10.1021/np9001948
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic Agents. 454. Synthesis of the Strong Cancer Cell Growth Inhibitors trans-Dihydronarciclasine and 7-Deoxy-trans-dihydronarciclasine

Abstract: To further pursue the antineoplastic leads offered by our isolation of trans-dihydronarciclasine (1a) and 7-deoxy-trans-dihydronarciclasine (1c) from two medicinal plant species of the Amaryllidaceae family, a practical palladium-catalyzed hydrogenation procedure was developed for synthesis of these isocarbostyrils from narciclasine (2a) and 7-deoxynarciclasine (2c).From a 1982 collection (bulbs) of the Chinese medicinal plant Zephyranthes candida (Amaryllidaceae) 1b we isolated the strong (ED 50 0.0032 μg/mL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…In a recent study, McNulty et al have demonstrated that narciclasine displays potent inhibitory activity against the human cytochrome CYP3A4, while trans ‐dihydronarciclasine is inactive with respect to CYP3A4, CYP19, and CYP1A1. The authors concluded that trans ‐dihydronarciclasine is a readily available substance with potent and selective anticancer activity, which is consistent with earlier results from the Pettit laboratory …”
Section: Structure‐activity Studies Of Narciclasine and Related Natursupporting
confidence: 87%
“…In a recent study, McNulty et al have demonstrated that narciclasine displays potent inhibitory activity against the human cytochrome CYP3A4, while trans ‐dihydronarciclasine is inactive with respect to CYP3A4, CYP19, and CYP1A1. The authors concluded that trans ‐dihydronarciclasine is a readily available substance with potent and selective anticancer activity, which is consistent with earlier results from the Pettit laboratory …”
Section: Structure‐activity Studies Of Narciclasine and Related Natursupporting
confidence: 87%
“…More recently, several isocarbostyril constituents of the Amaryllidaceae , such as narciclasine, pancratistatin, trara‐dihydronarciclasine, and their congeners (for structure examples, see Fig. ), have been isolated or semisynthesized (19, 20). Narciclasine, known for >40 yr, is isolated from narcissus bulbs and serves as an inhibitor of plant growth (21), which was first characterized for its antimitotic effects (22).…”
mentioning
confidence: 99%
“…The structurally minimum pharmacophore required for potent anticancer activity has been defined in the pancratistatin series of alkaloids based on a number of structure-activity correlations that have been conducted with both natural and synthetic analogues (37,38). The pharmacophore consists of the 2,3,4-triol structural element in ring-C.…”
Section: Discussionmentioning
confidence: 99%